Design of a Web-based Cold Storage Temperature Monitor with Arduino Uno for Fish Quality Maintenance: Sensor-based Methodology and Innovative Contribution - Hermawan, Ade; Andrian.Harahap, Doly Andrian; Daging, I Ketut; Dewi, Priyantini; Ridhwan, Rafif Zainun; Qadri, Munzir (Universitas Muhammadiyah Jakarta, 2023)
The development of a web-based cold storage temperature and humidity monitoring device using Arduino Uno aims to monitor room conditions, particularly in cold storage spaces, through a website. This device utilizes DHT11 and DS18B20 sensors, along with the Wemos D1 Mini module, integrated with the Arduino Uno microcontroller. Arduino configuration is performed through an application to send commands to other components. The research was conducted at PT. Indu Manis Gresik, East Java. Data collection and testing were carried out at the specified location. The test results demonstrate the device's efficient operation, transmitting testing data to the associated website. The accuracy of the DS18B20 temperature sensor testing reached 98.8%, while the DS18B20 humidity sensor achieved 99.35%.